A Green Approach to Synthesize Silver Nanoparticles in Starch-co-Poly(acrylamide) Hydrogels by Tridax procumbens Leaf Extract and Their Antibacterial Activity. (24th December 2013) - Shaik, Siraj; Kummara, Madhusudana Rao; Poluru, Sudhakar; Allu, Chandrababu; Gooty, Jaffer Mohiddin; Kashayi, Chowdoji Rao; Subha, Marata Chinna Subbarao
Abstract : A series of starch-co-poly(acrylamide) (starch-co-PAAm) hydrogels were synthesized by employing free radical redox polymerization. A novel green approach, Tridax procumbens (TD) leaf extract, was used for reduction of silver ions (Ag + ) into silver nanoparticles in the starch-co-PAAm hydrogel network. The formation of silver nanoparticles was confirmed by UV-visible spectroscopy (UV-Vis), thermogravimetric analysis (TGA), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (X-RD) studies. 22% of weight loss difference between hydrogel and silver nanocomposite hydrogel (SNCH) clearly indicates the formation of silver nanoparticles by TGA. TEM images indicate the successful incorporation of silver nanoparticles ranging from 5 to 10 nm in size and spherical in shape with a narrow size distribution. These developed SNCHs were used to study the antibacterial activity by inhibition zone method against gram-positive and gram-negative bacteria such as Bacillus and Escherichia coli . The results indicated that these SNCHs can be used potentially for biomedical applications.